Estudo experimental da inibição do VEGF na regeneração hepática - Sousa, Eros Luiz de (2019)
Background: extensive liver resections and transplants of liver parts are possible thanks to its regenerative capacity which is dependent on vascular endothelial growth factor (VEGF) activation which also regulates the angiogenesis. Bevacizumab (BV), a monoclonal antibody VEGF inhibitor, is a neoadjuvant treatment of cancers widely used, restricting microvascular density and may cause undesirable effects on postoperative healing and liver regeneration (LR). Objective: to determine the effect of a single dose (5mg/kg) of BV in LR. Methods: 32 rats submitted to partial hepatectomy (PH) were separated into two groups according to saline solution (C) or BV (BV) treatment. According to the observation time (48h and 15 days) they were subdivided in C48 and BV48 and C15 and BV15 sub-groups. In LR, the BV effects were evaluated by weight variation and liver function (albumin, transaminase, bilirubin and APRI ratio) and in remaining liver were evaluated, mitotic activity, microvascular density (angiogenesis), nuclear proliferation, histopathology for fibrosis, edema and congestion. For statistical analysis, the ANOVA and T-Student test was used (of statistical significance when p≤0.05). Results: on the fifteenth day after PH and BV treatment, there were no differences in weight evaluations (p=0.0691), liver function and mitotic indexes (p=0.1576). However, there was a decrease in cell viability (p=0.0000), microvascular density (p = 0.0162) and worsening in the occurrence of histopathological changes such as liver fibrosis, edema and congestion. Conclusion: a single BV dose, on the fifteenth day of evolution has no significant effect in weight evolution, serum biochemical evaluations (albumin, bilirubin and transaminases) and mitotic index. However, it induced microvascular density decreased, cell viability and liver histopathological changes such as fibrosis, edema and congestion.